PERENCANAAN ULANG BALOK BETON BERTULANG PADA GEDUNG RUSUNAWA UMM DENGAN METODE STRUT AND TIE - Fitrianti, Dona Dwi; Septiropa, Zamzami; Rommel, Erwin (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2011)
Deep beam is the reinforced concrete structure, which has loads like normal beam, but has acomparatively high rate / width of a large, with clean span of Ln equal to or less than four times theoverall member height (h) or twice effectively depth beam (2d ) from the face of support withconcentrated loading. Strut and Tie Model (STM) is a method used to find the balance between loadand reaction forces in the concrete and steel.Redesign on Rusunawa beams using deep beam structure that consists of, beam 0.9 mx0,3mwith length 6.8 m that loaded of concentrated loading and deep beam 1.3 mx0, 4m by 4.2 meterslong that uniformly distributed loading. quality of concrete is used 25 Mpa and the quality of Steel350 MpaFrom the results of planning by using Strut and Tie Model (STM), obtained main flexurereinforcement of 6.8 meters is 4D19 for tensile bar and 5D19 for assembling bar. and Ã˜8- 160mmfor horizontal and vertical stirrups. As for the deep beam spans 4.2 meters, obtained flexurereinforcement is 5D20 for tensile and assembling bar and Ã˜8 - 220.2 mm for horizontal and verticalstirrups.Keywords: Deep beam, Strut and Tie method